Peak Oxygen Uptake is Slope Dependent: Insights from Ground Reaction Forces and Muscle Oxygenation in Trained Male Runners - Marcel Lemire; Frédéric Meyer; Rosalie Triguera; Fabrice Favret; Grégoire P. Millet; Stéphane P. Dufour (SpringerOpen, 2024)
Abstract Background The aim of this study is to explore the effect of treadmill slope on ground reaction forces and local muscle oxygenation as putative limiting factors of peak oxygen uptake in graded maximal incremental running tests. Thirteen trained male runners completed five maximal incremental running tests on treadmill at − 15%, − 7.5%, 0%, 7.5% and 15% slopes while cardiorespiratory and local muscle oxygenation responses as well as ground reaction forces were continuously recorded. Blood lactate concentration and isometric knee extensor torque were measured before and after each test. Results Peak oxygen uptake was lower at − 15% slope compared to all other conditions (from − 10 to − 17% lower, p < 0.001), with no difference between − 7.5 and + 15% slope. Maximal heart rate and ventilation values were reached in all conditions. The negative external mechanical work increased from steep uphill to steep downhill slopes (from 6 to 92% of total external work) but was not correlated with the peak oxygen uptake reduction. Local muscle oxygenation remained higher in − 15% slope compared to level running (p = 0.003). Conclusions Similar peak oxygen uptake can be reached in downhill running up to − 7.5% slope. At more severe downhill slopes (i.e., − 15%), greater negative muscle work and limited local muscle deoxygenation occurred, even in subjects familiarized to downhill running, presumably preventing the achievement of similar to other condition's peak oxygen uptake. Key Points Trained male runners can reach like level running V̇O2peak at moderate but not at severe negative slope. Negative external mechanical work increases with increasing negative slope. At maximal intensity Vastus Lateralis muscle oxygenation is higher in steep negative slope. Knee extensor isometric muscle torque is preserved after maximal level and uphill running, but reduced after downhill running, despite lower blood lactate. Progressive reduction of V̇O2 at maximal effort with increasing negative slope might be related to the metabolic consequences of increased lower limb negative external work (i.e., eccentric muscle actions).